(NpRAKTI^ESKIJ KURS RUSSKOGO QZYKA (B:s (Nu^EBNOE POSOBIE (B/s - (NaZIMOWA(B, (NaRZYGULX dOWRANOWNA(B.s; (NaLIEWA(B, (NtAMRIS nAGIEWNAs; (NeR[OWA(B, (NeWGENIQ nIKOLAEWNAs ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 316s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NrUSSKIJ QZYK DLQ NERUSSKIHs